Development of the Methodology for Assessing the Level of Innovative Potential of an Industrial Enterprise - M. V. Apanasevich (Цифровая трансформация)
The success of any modern company is largely determined by its focus on development, innovation becomes an integral part of its activities. The choice of innovative development’s direction is predetermined by the potential it has, and therefore it is extremely important to understand the essence of this definition. The article considers the essence and content of the concept of “innovation potential”. Common approaches to its definition and evaluation methods are highlighted, their advantages and disadvantages are revealed. The author’s interpretation of the innovative potential of an industrial enterprise is proposed and a new method of its assessment is presented. The significance of this article lies in the today’s absence of such a methodology for assessing the innovation potential. Unlike the existing ones, the new methodology proposed by the author allows to take into account different degrees of influence of structural indicators on the resulting one due to the presence of weighting coefficients; to minimize the subjectivity factor when scoring; to conduct a comprehensive analysis of the company’s condition through a comprehensive assessment of indicators, the structural components of which have different measurement values; to determine the prospects based on the dynamics of indicators and to form strategies for the company’s development.